A rare case of malignant peripheral nerve sheath tumor of pleura and review of literature - B P Amrith; Sunil Pasricha; Ankush Jajodia; Venkata Pradeep Babu Koyyala; Ullas Batra (Wolters Kluwer Medknow Publications, 2021)
Malignant peripheral nerve sheath tumor (MPNST) is a type of soft tissue sarcoma arising from peripheral nerves. They can be found in isolation, but about half of the cases are associated with neurofibromatosis type 1 (NF1), an autosomal dominant genetic disorder. They usually arise from the nerve plexus in extremities and trunk. MPNSTs arising from the viscera or internal organs are very rare. We hereby report a rare case of sporadic MPNST arising from pleural surface in a middle-aged male. The diagnosis of such a rare entity involved multimodal investigations with consideration of wide differential diagnosis.